Short-term exposure to a high-humidity environment triggers intestinal inflammation via AQP3 - Jian Song; Jian Song; Jian Song; Xinhua Huang; Xinhua Huang; Xinhua Huang; Yi Luo; Yi Luo; Yi Luo; Mengjun Li; Mengjun Li; Mengjun Li; et al. (Frontiers in Immunology, 2025)
BackgroundWith the increasing greenhouse effect, there is growing concern about the correlation between the humid environment and the incidence of various diseases. A high-humidity environment may cause intestinal inflammation through bacterial colonization or contamination of water. Aquaporin-3 (AQP3) plays an important role in maintaining intestinal water transport, permeability, fluid secretion, and absorption homeostasis. This paper explored the effects of short-term exposure to a high-humidity environment on intestinal health.MethodsTo explore the effects of a high-humidity environment on the intestine, we kept wild-type mice and Aqp3 knockout (Aqp3-/-) mice in an artificial climatic box with 90(± 5) % humidity setting for a fortnight and recorded their body weights, food intake, water intake, and fur changes during the experiment. On the fourteenth day, colon tissues were collected to detect the expression of intestinal inflammatory factors, glutathione (GSH), malondialdehyde (MDA), water evaporator proteins (AQPs), and intestinal pathological changes by polymerase chain reaction (PCR), Western blotting analysis, and histopathological analysis.ResultsThe results showed that mice with short-term exposure to a high-humidity environment showed a significant increase in the expression of AQP3 and a significant decrease in the expression of AQP4 in the colon, and the TLR4/NF-κb/IL-6 pathway was activated. In Aqp3-/- mice, their colonic GSH expression was increased, MDA expression was decreased, and intestinal TLR4/NF-κb/IL-6 expressions were also decreased.ConclusionsThis study demonstrated the high-humidity environment induces an intestinal inflammatory response through AQP3, providing persuasive evidence for the pathogenesis of environmentally related diseases.